Silicon-carbon composite material, preparation method, secondary battery and electric device
By designing the composite structure of silicon-containing material particles and carbon-based material particles, and using spray granulation technology and carbon cladding technology, the problems of poor energy density, storage performance and cycle stability of existing silicon-carbon composite materials in secondary batteries are solved, achieving efficient battery performance improvement.
Patent Information
- Application Number
- CN202311640839.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-11-30
AI Technical Summary
Existing silicon-carbon composite materials are difficult to take into account high energy density, storage performance and cycle stability in secondary batteries, and are particularly poor in high temperature conditions.
By designing the internal area of the silicon-carbon composite material, it is mainly composed of high-capacity silicon-containing material particles, and the external area is mainly composed of carbon-based material particles. The secondary particles are prepared by spray granulation technology to form a tightly coated structure to isolate the contact between silicon and electrolyte, and reduce the specific surface area through the carbon cladding layer.
It realizes high storage performance and cycle stability of secondary batteries under high temperature conditions, while also having excellent energy density, extending the service life of the battery.
Smart Images

Figure CN119852339A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a silicon-carbon composite material, a preparation method, a secondary battery and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] With the popularization of secondary battery applications, higher requirements are also placed on their energy density. Silicon-carbon composite materials can improve the energy density of batteries, but they often deteriorate the storage performance and cycle performance of batteries, so existing silicon-carbon composite materials still need to be improved. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a silicon-carbon composite material, which has excellent specific capacity and can improve the high-temperature storage performance and cycle stability of the battery.
[0005] A first aspect of the present application provides a silicon-carbon composite material, which includes an inner region and an outer region, wherein the inner region is mainly composed of silicon-containing material particles, and the outer region is mainly composed of carbon-based material particles.
[0006] Silicon has a higher specific capacity than carbon-based materials, but its surface reactivity is high, and the electrolyte is easily decomposed on the surface of the silicon negative electrode, resulting in a decrease in its storage performance. And the mechanism of lithium storage in the silicon negative electrode determines that it will undergo huge volume expansion and contraction during the process of lithium extraction, which will not only deteriorate the cycle performance of the battery, but also cause the solid electrolyte interface film (SEI film) to continuously crack and generate, and continuously consume active ions, further deteriorating the storage performance of the battery. Compared with silicon, carbon-based materials have low surface activity and structural stability, but they cannot further improve the energy density of the battery. Therefore, the silicon-carbon composite material provided in the present application is prepared by preparing high-capacity silicon-containing materials and carbon-based materials with excellent storage life into secondary particles whose internal regions are mainly silicon-containing material particles and whose external regions are mainly carbon-based material particles. While making the battery have excellent energy density, by reducing the surface activity of the silicon-carbon composite material, isolating silicon from the contact with the electrolyte, improving the storage performance of the battery, and the carbon-based material particles in the external region have higher strength, which has an inhibitory effect on the volume expansion of silicon-containing material particles, improving the structural stability of the silicon-carbon composite material, and further improving the cycle stability of the battery.
[0007] Compared with silicon-carbon composite materials in which silicon-containing material particles and carbon-based material particles are directly mixed or used in the form of uniformly distributed secondary particles, the silicon-carbon composite material of the present application can not only isolate the contact between silicon and the electrolyte, but also reserve space for the volume expansion of the silicon-containing material particles by reserving gaps, thereby improving the storage performance and cycle stability of the battery while taking into account the excellent energy density.
[0008] In any embodiment, the number of silicon-containing material particles in the inner region is less than or equal to 3, and can be 1-2.
[0009] When the number of silicon-containing material particles in the internal area is within the above range, it is beneficial for the carbon-based material particles to densely wrap the silicon-containing material particles and control the particle size of the finished silicon-carbon composite material within an appropriate range, thereby reducing the contact between silicon and the electrolyte and improving the battery's kinetic performance. At the same time, it also meets the processing performance requirements of the silicon-carbon composite material during negative electrode slurry homogenization and negative electrode sheet coating, so that the battery has excellent storage performance, cycle stability and kinetic performance.
[0010] In any embodiment, the mass proportion of silicon element in the region r / 2 from the geometric center of the silicon-carbon composite material is greater than or equal to 30%, and can be optionally 35%-45%, wherein r represents the short diameter of the silicon-carbon composite material.
[0011] When the mass proportion of silicon element in the region r / 2 away from the geometric center of the silicon-carbon composite material is within the above range, the battery can have excellent energy density, storage performance and cycle stability.
[0012] In any embodiment, the mass proportion of carbon element in the region extending from the outer surface of the silicon-carbon composite material to the inside by a distance r / 2 is greater than or equal to 80%, and can be optionally 90%-100%, wherein r represents the short diameter of the silicon-carbon composite material.
[0013] When the mass proportion of carbon elements in the area extending from the outer surface of the silicon-carbon composite material to the inside by a distance of r / 2 is within the above range, the silicon-carbon composite material can isolate silicon from contact with the electrolyte, inhibit the volume change of silicon during the process of lithium insertion and extraction, and improve the storage performance and cycle stability of the battery.
[0014] In any embodiment, the outer region of the silicon-carbon composite material further comprises an amorphous carbon coating layer.
[0015] The amorphous carbon coating in the external region can further isolate silicon from contact with the electrolyte and reduce the specific surface area of the silicon-carbon composite material, thereby preventing the prepared secondary particles from having an uneven surface that leads to an excessively large specific surface area of the silicon-carbon composite material, increasing the area in contact with the electrolyte, and the amount of active ions consumed in generating the SEI film, thereby comprehensively improving the storage performance, cycle stability and initial efficiency of the battery.
[0016] In any embodiment, the Dv50 of the silicon-containing material particles is greater than or equal to the Dv50 of the carbon-based material particles.
[0017] The Dv50 of the silicon-containing material particles is greater than or equal to the Dv50 of the carbon-based material particles, which is beneficial to improving the integrity of the carbon-based material particles coating the silicon-containing material particles, thereby improving the storage performance of the battery.
[0018] In any embodiment, the Dv50 of the silicon-containing material particles is less than or equal to 5 μm.
[0019] When the Dv50 of the silicon-containing material particles is within the above range, it is beneficial to control the particle size of the finished silicon-carbon composite material within an appropriate range, and it has good pole piece processing performance and dynamic performance.
[0020] In any embodiment, the carbon-based material particles have a Dv50 of less than or equal to 5 μm.
[0021] When the particle size of the carbon-based material particles is within the above range, the integrity of the carbon-based material particles coating the silicon-containing material particles can be improved, and it is beneficial to control the particle size of the finished silicon-carbon composite material within an appropriate range, meet the performance requirements of the electrode processing, and improve the storage performance and dynamic performance of the battery.
[0022] In any embodiment, the silicon-containing material particles include at least one of elemental silicon, silicon-oxygen material, silicon-carbon material, and silicon-metal alloy. Optionally, the silicon-containing material particles include silicon-carbon material.
[0023] In any embodiment, the carbon-based material particles include at least one of artificial graphite and natural graphite. Optionally, the carbon-based material particles include artificial graphite.
[0024] In any embodiment, the silicon-containing material particles include a carbon substrate having a pore structure and a silicon-based material disposed in the pore structure of the carbon substrate.
[0025] The pore structure of the carbon substrate provides attachment sites for silicon-based materials, which can be used to store a large amount of silicon. The silicon-based materials uniformly dispersed in the pore structure of the carbon substrate are not easy to agglomerate. Furthermore, the carbon substrate has a certain mitigating effect on the volume change of the silicon-based materials arranged in the pore structure during the lithium insertion and extraction process, and can withstand the stress caused by the volume change of the silicon-based materials, so that the silicon-containing material particles have a low expansion rate and a highly stable structure, thereby improving the capacity, storage performance and cycle stability of the silicon-containing material particles. The internal area of the silicon-carbon composite material contains silicon-containing material particles of the above structure, which can not only improve the capacity of the battery, but also avoid the cracking of the silicon-carbon composite material during the cycle due to excessive volume expansion of the internal area, thereby improving the storage performance and cycle stability of the battery.
[0026] In any embodiment, the pore structure includes micropores with a pore size less than 2 nm, mesopores with a pore size of 2 nm-50 nm, and macropores with a pore size greater than 50 nm.
[0027] The above-mentioned pore structure in the carbon substrate helps the silicon-based material to adhere to the pore structure, and can effectively limit the volume expansion of the silicon-based material attached to the pore structure. Moreover, the silicon-based material after volume expansion will basically not cause damage to the pore structure of the carbon matrix, thereby increasing the capacity of the silicon-containing material particles while ensuring the stability of the structure.
[0028] In any embodiment, the pore volume of the micropores is greater than or equal to 0.5 cm 3 / g, optional 0.6cm 3 / g-0.9cm 3 / g.
[0029] By regulating the pore volume size of the micropores in the carbon substrate, it is beneficial for the silicon-containing precursor to enter the pore structure of the carbon substrate, reducing the risk of silicon deposition on the surface of the carbon substrate, and improving the gram capacity and storage performance of the silicon-containing material particles.
[0030] In any embodiment, the average pore diameter of the carbon substrate is less than or equal to 5 nm, and can be 1 nm-3.5 nm.
[0031] When the average pore size of the carbon substrate is within the above range, it is helpful for the adhesion of silicon-based materials, and the carbon substrate can limit the volume expansion of the silicon-based materials in the pores. The expanded silicon-based materials will not cause damage to the porous carbon matrix structure, thereby improving the capacity and structural stability of the silicon-containing material particles, and the battery has excellent storage performance and cycle stability.
[0032] In any embodiment, the specific surface area of the carbon substrate is greater than or equal to 1200 m 2 / g, optional 1500m 2 / g-1800m 2 / g.
[0033] The specific surface area of the carbon substrate is within the above range. The carbon substrate has excellent pore volume and provides many sites for the deposition of silicon-based materials, which is beneficial to increasing the gram capacity of silicon-containing material particles.
[0034] In any embodiment, the silicon-based material includes at least one of elemental silicon, silicon-oxygen material, silicon-carbon material, and silicon-metal alloy; the carbon substrate includes at least one of graphite, soft carbon, and hard carbon.
[0035] In any embodiment, the silicon-based material particles include silicon grains. Optionally, the size of the silicon grains is less than or equal to 10 nm. Optionally, the size of the silicon grains is less than or equal to 3 nm.
[0036] The size of silicon grains within the above range can avoid excessive local silicon enrichment due to excessive grain size, which may cause large expansion of silicon-containing material particles during lithium insertion and lead to cracking of the material, thereby improving the storage performance and cycle stability of the battery.
[0037] In any embodiment, the porosity of the silicon-carbon composite material is 20%-45%, and optionally 20%-35%.
[0038] The porosity of the silicon-carbon composite material is within the above range, which reserves space for the volume change that occurs when the silicon-based material particles in the internal area insert and extract lithium. While taking into account the excellent gram capacity, the structural stability of the silicon-carbon composite material can be improved, thereby improving the energy density, storage performance and cycle stability of the battery.
[0039] In any embodiment, the volume distribution particle size Dv50 of the silicon-carbon composite material is less than or equal to 16 μm, and can be optionally 8 μm-16 μm.
[0040] When the Dv50 of the silicon-carbon composite material is within the above range, the material has excellent dynamic properties and electrode processing performance, which is beneficial to improving the storage performance and cycle stability of the battery.
[0041] In any embodiment, the particle size distribution of the silicon-carbon composite material is (Dv90-Dv10) / Dv50 of 0.5-1.8, and can be optionally 0.8-1.5.
[0042] When the particle size distribution of the silicon-carbon composite material is within the above range, the overall average particle size of the silicon-carbon composite material is relatively moderate, and the particle size distribution is relatively even, which is beneficial to improving the uniformity of the overall performance of the silicon-carbon composite material.
[0043] In any embodiment, the powder compaction density of the silicon-carbon composite material at 49000N is 0.7g / cm 3 -1.3g / cm 3 , optional 0.95g / cm 3 -1.1g / cm 3 .
[0044] When the powder compaction density of the silicon-carbon composite material is within the above range, the negative electrode sheet has a higher compaction density, thereby further improving the energy density of the battery. In addition, the negative electrode film layer has a stronger ability to maintain the pore structure during the cycle, and the electrolyte wettability of the negative electrode sheet is better, which is conducive to improving the storage performance and cycle stability of the battery.
[0045] In any embodiment, the specific surface area of the silicon-carbon composite material is less than or equal to 6 m 2 / g, can be selected to be less than or equal to 4.5m 2 / g.
[0046] When the specific surface area of the silicon-carbon composite material is within the above range, it helps to further reduce the contact area between the silicon-carbon composite material and the electrolyte, reduce the consumption of active ions in forming the SEI film, and improve the initial efficiency, storage performance and cycle stability of the battery.
[0047] The second aspect of the present application provides a method for preparing a silicon-carbon composite material, comprising the following steps: providing silicon-containing material particles and carbon-based material particles; subjecting the silicon-containing material particles and a binder to a first spray granulation to obtain a first intermediate product; spraying the carbon-based material particles onto the surface of the first intermediate product to perform a second spray granulation to prepare a silicon-carbon composite material; wherein the silicon-carbon composite material comprises an inner region and an outer region, the inner region is mainly composed of silicon-containing material particles, and the outer region is mainly composed of carbon-based material particles.
[0048] By subjecting the silicon-containing material particles and the binder to a first spray granulation, the particle size of the silicon-containing material particles in the internal area of the silicon-carbon composite material can be controlled to obtain a first intermediate product in which the silicon-containing material particles are uniformly coated with the binder on the outside. By subjecting the carbon-based material particles to a second spray granulation and spraying them onto the surface of the first intermediate product, secondary particles can be obtained in which the inside is mainly silicon-containing material particles and the outside is mainly carbon-based material particles, and the carbon-based material particles tightly coat the silicon-containing material particles. Through two-step granulation, compared with the preparation method of simultaneously mixing and granulating silicon-containing material particles, a binder, and carbon-based material particles, the preparation method of the present application can achieve a state in which the silicon-containing material particles are completely coated by the carbon-based material particles, isolating the silicon from the contact with the electrolyte, and can regulate the porosity of the silicon-carbon composite material, thereby improving the storage performance and cycle stability of the battery.
[0049] In any embodiment, silicon-containing material particles are prepared by the following steps: providing a gas containing a silicon precursor to a carbon substrate having a porous structure; and generating a silicon-based material attached to the porous structure from the silicon precursor by chemical vapor deposition to obtain silicon-containing material particles.
[0050] In any embodiment, the mass ratio of the silicon-containing particles to the binder is 1:2-2:1.
[0051] When the mass ratio of silicon-containing material particles to adhesive is within the above range, the silicon-containing material particles and the carbon-based material particles have a good bonding effect, the particle size of the finished silicon-carbon composite material is within an appropriate range, and the battery has good storage performance and cycle stability while having excellent energy density.
[0052] In any embodiment, the mass ratio of the silicon-containing particles to the carbon-based material particles is 1:12-1:6.
[0053] When the mass ratio of silicon-containing material particles to carbon-based material particles is within the above range, the carbon-based material particles form a complete coating layer on the surface of the silicon-containing material particles to isolate silicon from the contact with the electrolyte, and the silicon-carbon composite material will not reduce its gram capacity due to excessive coating caused by an excessively high proportion of carbon-based material particles. The battery has excellent energy density, storage performance and cycle stability.
[0054] In any embodiment, the temperature difference between the inlet air temperature and the outlet air temperature of the first spray granulation is not greater than 60°C.
[0055] Spray granulation relies on hot air drying of materials, and the drying state of the intermediate product is controlled by controlling the temperature of the hot air. Since the temperature of hot air drying is greatly affected by the environment, and the chamber only has a certain insulation effect but no heating effect, the temperature in the chamber is not an accurate temperature, but a temperature range. Setting the difference between the inlet and outlet temperatures within this range can ensure that the chamber temperature is within the appropriate range, and the actual temperature in the chamber will not be too low due to excessive temperature difference.
[0056] In any embodiment, the inlet air temperature of the first spray granulation is 110°C-150°C.
[0057] The temperature of the incoming air is the initial heat source in the chamber. Spray granulation relies on the incoming air to dry the material, ensuring that the silicon-containing material particles wrapped in the binder are in a semi-dry state, and preventing the silicon-containing material particles from sticking together due to excessive moisture due to low temperature, resulting in a larger particle size of the silicon-containing material in the inner area of the finished silicon-carbon composite material, and then the particle size of the finished silicon-carbon composite material is larger; or the temperature is too high and too dry to proceed to the next process. When the inlet air temperature is within the above range, the silicon-carbon composite material has good dynamic performance and pole piece processing performance.
[0058] In any embodiment, the outlet air temperature of the first spray granulation is 50°C-90°C.
[0059] The outlet air temperature is the result of comprehensive consideration of heat, which is determined by the inlet air temperature, feed rate, etc. Setting the outlet air temperature of the first spray granulation within this range can avoid the large temperature difference with the inlet air temperature causing the temperature in the chamber to be too low, and can also further make the first intermediate product in a semi-dry state, which is conducive to the next process.
[0060] In any embodiment, the feed gas pressure of the first spray granulation is 250 KPa-350 KPa, and can be optionally 280 KPa-320 KPa.
[0061] The feed air pressure of the first spray granulation is a key step in controlling the particle size of the finished silicon-carbon composite material. When the feed air pressure is within the above range, the number and particle size of the silicon-containing material particles sprayed out can be controlled within an appropriate range to avoid the silicon-containing material particles being too large due to too low air pressure, which in turn causes the silicon-carbon composite material to have too large a particle size, deteriorating the dynamic performance and pole piece processing performance of the silicon-carbon composite material, and also avoiding the situation where some silicon-containing material particles are blocked at the spray gun nozzle and cannot be sprayed out due to too high air pressure. When the feed air pressure of the first spray granulation is within the above range, the particle size of the silicon-containing material sprayed out can be within an appropriate range, reaching a state where the number of silicon-containing material particles in the internal area of the silicon-carbon composite material does not exceed 3, which is beneficial to improving the storage performance and pole piece processing performance of the silicon-carbon composite material.
[0062] In any embodiment, the temperature difference between the inlet air temperature and the outlet air temperature of the second spray granulation is 20°C-40°C.
[0063] In any embodiment, the inlet air temperature of the second spray granulation is 170°C-280°C.
[0064] The air inlet temperature of the second spray granulation step is a key step in controlling the strength and structural stability of the silicon-carbon composite material. Since the first intermediate product has a certain viscosity, it is necessary to quickly coat the carbon-based material particles to form secondary particles and dry them to avoid the first intermediate product and secondary particles from agglomerating or bonding together during the process due to low temperature. It can also avoid the binder shrinking too fast or failing due to high temperature, which will not produce a good bonding effect. When the air inlet temperature of the second spray granulation is within this range, the prepared silicon-carbon composite material has a suitable particle size, excellent strength and structural stability, and plays a role in stabilizing the storage performance and cycle performance during the battery's life cycle.
[0065] In any embodiment, the outlet air temperature of the second spray granulation is 130°C-240°C.
[0066] In any embodiment, the feed gas pressure of the second spray granulation is 150 KPa-260 KPa, and can be optionally 180 KPa-210 KPa.
[0067] The feed air pressure of the second spray granulation is a key step in controlling the integrity and uniformity of the carbon-based material particles coating the silicon-containing material particles. The feed air pressure of the second spray granulation is within the above range, which can improve the storage performance and cycle stability of the battery. It can avoid the excessive air pressure and too fast feed speed, which leads to too many carbon-based material particles wrapped around the outside of the silicon-containing material, and the large particle size of the finished silicon-carbon composite material, thereby deteriorating the dynamic performance, electrode processing performance and gram capacity of the silicon-carbon composite material; it can also avoid the air pressure being too low and the feed speed being too slow, which leads to some silicon-containing material particles not being completely coated by the carbon-based material particles, and the inability to completely isolate the silicon from the electrolyte, thereby weakening the storage performance of the silicon-carbon composite material.
[0068] In any embodiment, the method for preparing the silicon-carbon composite material further comprises: introducing a gaseous carbon source after the second spray granulation, and carbonizing the gaseous carbon source after gas-phase coating to obtain the silicon-carbon composite material.
[0069] The secondary particles formed by coating the silicon-containing material with carbon-based material particles have more bumps on the surface and a larger specific surface area. After carbon coating, the specific surface area of the silicon-carbon composite material can be controlled within an appropriate range, so that the battery has excellent storage performance, cycle stability and first effect; and the carbon coating layer in the external area can further reduce the possibility of contact between silicon and electrolyte, and the storage performance of the battery is further improved.
[0070] In any embodiment, the gaseous carbon source includes a gaseous hydrocarbon alkane, which may be at least one of methane, ethylene, and acetylene.
[0071] The temperature at which the gaseous carbon source decomposes to form the carbon coating layer is within a suitable range, satisfying the temperature requirements of various components of the silicon-carbon composite material.
[0072] In any embodiment, the carbonization temperature is 400°C-800°C.
[0073] When the carbonization temperature is within the above range, the gaseous carbon source can decompose to produce carbides that coat the surface of the secondary particles to form a carbon coating layer, which can reduce the specific surface area of the secondary particles while further isolating the contact between silicon and the electrolyte, thereby improving the storage performance and cycle stability of the battery; it can also avoid the silicon in the silicon-containing material particles from generating silicon carbide that cannot provide capacity due to excessively high temperature, thereby achieving the purpose of not losing the gram capacity of the silicon-carbon composite material.
[0074] In any embodiment, the carbonization time is 0.2 h-2 h.
[0075] When the carbonization time is within the above range, the silicon-carbon composite material has a suitable specific surface area and excellent capacity, which can avoid the problem that the amorphous carbon coating is too small due to too short a time, and the surface of the secondary particles cannot be completely covered to achieve the purpose of reducing the specific surface area; it can also avoid the problem that the carbonization time is too long, which greatly increases the risk of silicon generating silicon carbide under long-term high temperature, resulting in loss of capacity of the silicon-carbon composite material.
[0076] In any embodiment, the protective gas during the carbonization process is nitrogen or argon. Optionally, the gas flow ratio of the gaseous carbon source to the protective gas is 1:5 to 1:1.5.
[0077] When the airflow ratio of the gaseous carbon source to the protective gas is within the above range, the silicon-carbon composite material has excellent processing efficiency and suitable specific surface area, which can avoid the long coating time and slow production efficiency caused by the too low airflow ratio; and can also avoid the too high airflow ratio, which leads to the gaseous carbon source decomposing too quickly, and is easy to be locally enriched on the surface of the secondary particles, and cannot form a uniform amorphous carbon coating layer, and cannot effectively reduce the specific surface area of the silicon-carbon composite material.
[0078] In any embodiment, the binder includes at least one of phenolic resin, styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, sodium alginate, carboxymethyl cellulose, polyacrylonitrile, and polypropylene alcohol.
[0079] On the one hand, the above-mentioned adhesive can provide bonding force between the silicon-containing material particles and the carbon-based material particles. On the other hand, it will shrink due to heat in the second spray granulation step to form pores and retain functional groups that exert bonding properties and remove volatiles in the carbonization step, so that the silicon-carbon composite material has a certain porosity, reserving space for the expansion of the silicon-containing material particles, thereby improving the storage performance and cycle stability of the battery.
[0080] A third aspect of the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises the silicon-carbon composite material of the first aspect or the silicon-carbon composite material prepared by the preparation method of the second aspect.
[0081] The fourth aspect of the present application further provides an electrical device, comprising the secondary battery of the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Figure 1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0083] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0084] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0085] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0086] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0087] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0088] Description of reference numerals:
[0089] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0090] Hereinafter, the embodiments of the silicon-carbon composite material, preparation method, secondary battery and electrical device of the present application will be specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0091] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0092] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0093] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0094] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0095] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0096] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0097] With the extension of the application scope of secondary batteries, the requirements for secondary battery performance, such as energy density, are gradually increasing. The negative electrode active material has a significant impact on the energy density of secondary batteries. Silicon-carbon composite materials, as a new type of negative electrode material, can effectively improve the energy density of batteries and have been widely studied. However, in traditional silicon-carbon composite materials, silicon-containing materials and carbon-based materials are usually in a state of uniform distribution or direct mixing, that is, the part of the silicon-carbon composite material in contact with the electrolyte also contains silicon, which causes silicon to continuously react with the electrolyte, consumes active ions, and deteriorates the storage performance and cycle performance of the battery.
[0098] [Silicon Carbon Composite Materials]
[0099] Based on this, the present application provides a silicon-carbon composite material, which includes an inner region and an outer region, wherein the inner region is mainly composed of silicon-containing material particles, and the outer region is mainly composed of carbon-based material particles.
[0100] In some embodiments, the silicon-containing material particles include at least one of elemental silicon, silicon-oxygen material, silicon-carbon material, and silicon-metal alloy.
[0101] In some embodiments, the silicon-containing material particles include silicon-carbon material.
[0102] In some embodiments, the carbon-based material particles include at least one of artificial graphite and natural graphite.
[0103] In some embodiments, the carbon-based material particles include artificial graphite.
[0104] As used herein, the term "silicon-carbon composite material" refers to a composite material composed of two elements, silicon and carbon.
[0105] Silicon has a higher specific capacity than carbon-based materials, but its surface reactivity is high, and the electrolyte is easily decomposed on the surface of the silicon negative electrode, resulting in a decrease in its storage performance. And the mechanism of lithium storage in the silicon negative electrode determines that it will undergo huge volume expansion and contraction during the process of lithium extraction, which will not only deteriorate the cycle performance of the battery, but also cause the solid electrolyte interface film (SEI film) to continuously crack and generate, and continuously consume active ions, further deteriorating the storage performance of the battery. Compared with silicon, carbon-based materials have low surface activity and structural stability, but they cannot further improve the energy density of the battery. Therefore, the silicon-carbon composite material provided in the present application is prepared by preparing high-capacity silicon-containing materials and carbon-based materials with excellent storage life into secondary particles whose internal regions are mainly silicon-containing material particles and whose external regions are mainly carbon-based material particles. While making the battery have excellent energy density, by reducing the surface activity of the silicon-carbon composite material, isolating silicon from the contact with the electrolyte, improving the storage performance of the battery, and the carbon-based material particles in the external region have higher strength, which has an inhibitory effect on the volume expansion of silicon-containing material particles, improving the structural stability of the silicon-carbon composite material, and further improving the cycle stability of the battery.
[0106] Compared with silicon-carbon composite materials in which silicon-containing material particles and carbon-based material particles are directly mixed or used in the form of uniformly distributed secondary particles, the silicon-carbon composite material of the present application can not only isolate the contact between silicon and the electrolyte, but also reserve space for the volume expansion of the silicon-containing material particles by reserving gaps, thereby improving the storage performance and cycle stability of the battery while taking into account the excellent energy density.
[0107] In some embodiments, the number of silicon-containing material particles in the inner region is less than or equal to 3, and may be 1-2.
[0108] The number of silicon-containing material particles in the internal area can be tested by methods known in the art. As an example, an argon ion beam is used to cut the silicon-carbon composite material perpendicular to the large surface of the silicon-carbon composite material to expose the cross section, and the cross section is photographed using a scanning electron microscope to observe the number of silicon-containing material particles in the internal area.
[0109] In some embodiments, the number of silicon-containing material particles in the inner region is 1, 2, or 3.
[0110] When the number of silicon-containing material particles in the internal area is within the above range, it is beneficial for the carbon-based material particles to densely wrap the silicon-containing material particles and control the particle size of the finished silicon-carbon composite material within an appropriate range, thereby reducing the contact between silicon and the electrolyte and improving the battery's kinetic performance. At the same time, it also meets the processing performance requirements of the silicon-carbon composite material during negative electrode slurry homogenization and negative electrode sheet coating, so that the battery has excellent storage performance, cycle stability and kinetic performance.
[0111] In some embodiments, the mass proportion of silicon element in the region r / 2 from the geometric center of the silicon-carbon composite material is greater than or equal to 30%, and can be optionally 35%-45%, wherein r represents the short diameter of the silicon-carbon composite material.
[0112] In some embodiments, the mass proportion of carbon elements in the region extending from the outer surface of the silicon-carbon composite material to the inside by a distance r / 2 is greater than or equal to 80%, and can be optionally 90%-100%, wherein r represents the short diameter of the silicon-carbon composite material.
[0113] The short diameter of the silicon-carbon composite material can be measured according to the three-axis characterization method, as follows: the short diameter r is measured on the plane projection diagram of the negative electrode material.
[0114] The mass percentage of silicon in the area r / 2 from the geometric center of the silicon-carbon composite material and the mass percentage of carbon in the area extending from the outer surface to the inside at a distance of r / 2 can be tested by methods known in the art. As an example, ion polishing cross-sectional element analysis (CP) is used in accordance with GB-T17359-2012 standard. According to the CP element spectrum of a single particle, the distribution position of Si and C elements can be determined. The content of silicon and carbon in the range from the geometric center to 1 / 2r can be directly tested in the corresponding area of the particle. The carbon content in the range from 1 / 2r to r is calculated as follows: the carbon content of the whole particle tested by the CP element is A, the carbon content in the range from the center of the circle to 1 / 2r is B, and the carbon content in the range from 1 / 2r to r is C.
[0115]
[0116] In some embodiments, the mass percentage of silicon element in the silicon-carbon composite material within the region r / 2 from the geometric center is 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45% or any numerical range therebetween.
[0117] When the mass proportion of silicon element in the region r / 2 away from the geometric center of the silicon-carbon composite material is within the above range, the battery can have excellent energy density, storage performance and cycle stability.
[0118] In some embodiments, the mass percentage of carbon element in the region extending from the outer surface of the silicon-carbon composite material to the inner side by a distance r / 2 is 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 100% or any numerical range therebetween.
[0119] When the mass proportion of carbon elements in the area extending from the outer surface of the silicon-carbon composite material to the inside by a distance of r / 2 is within the above range, the silicon-carbon composite material can isolate silicon from contact with the electrolyte, inhibit the volume change of silicon during the process of lithium insertion and extraction, and improve the storage performance and cycle stability of the battery.
[0120] In some embodiments, the outer region of the silicon-carbon composite material further includes an amorphous carbon coating layer.
[0121] In this article, the term "amorphous carbon" refers to a non-crystalline structure composed of carbon elements. Its mixed structure of sp3 and sp2 hybridization makes it different from the crystalline carbon of the crystalline system and has a structure and properties similar to an amorphous object (such as glass).
[0122] The amorphous carbon herein can be formed by carbonizing a gaseous carbon source, which can be any gas known in the art suitable for coating, for example, at least one of methane, ethylene, and acetylene.
[0123] The amorphous carbon coating in the external region can further isolate silicon from contact with the electrolyte and reduce the specific surface area of the silicon-carbon composite material, thereby preventing the prepared secondary particles from having an uneven surface that leads to an excessively large specific surface area of the silicon-carbon composite material, increasing the area in contact with the electrolyte, and the amount of active ions consumed in generating the SEI film, thereby comprehensively improving the storage performance, cycle stability and initial efficiency of the battery.
[0124] In some embodiments, the Dv50 of the silicon-containing material particles is greater than or equal to the Dv50 of the carbon-based material particles.
[0125] As used herein, the terms “Dv50”, “Dv90” and “Dv10” refer to the particle sizes corresponding to the cumulative volume distribution number of particles reaching 50%, 90% and 10% in the particle size distribution curve.
[0126] In this application, Dv50, Dv90, and Dv10 can be tested by methods known in the art. As an example, referring to GB / T 19077-2016 particle size distribution laser diffraction method, 0.1g to 0.13g of sample is weighed in a 50mL beaker, and 5g of anhydrous ethanol is weighed, added to the beaker containing the sample, and a stirring bar of about 2.5mm in length is placed, and sealed with plastic wrap. The sample is placed in an ultrasonic machine for 5min, transferred to a magnetic stirrer and stirred at a speed of 500r / min for more than 20min. Two samples are taken from each batch of products for testing, and the particle size distribution is measured to obtain the Dv50, Dv90, and Dv10 of the sample. It is conveniently measured using a laser particle size analyzer, such as the Malvern Mastersizer 3000 laser particle size analyzer of Malvern Instrument Co., Ltd., UK.
[0127] The Dv50 of the silicon-containing material particles is greater than or equal to the Dv50 of the carbon-based material particles, which is beneficial to improving the integrity of the carbon-based material particles coating the silicon-containing material particles, thereby improving the storage performance of the battery.
[0128] In some embodiments, the Dv50 of the silicon-containing material particles is less than or equal to 5 μm.
[0129] In some embodiments, the Dv50 of the silicon-containing material particles is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any range therebetween.
[0130] When the Dv50 of the silicon-containing material particles is within the above range, it is beneficial to control the particle size of the finished silicon-carbon composite material within an appropriate range, and it has good pole piece processing performance and dynamic performance.
[0131] In some embodiments, the Dv50 of the carbon-based material particles is less than or equal to 5 μm.
[0132] In some embodiments, the Dv50 of the carbon-based material particles is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any range therebetween.
[0133] When the particle size of the carbon-based material particles is within the above range, the integrity of the carbon-based material particles coating the silicon-containing material particles can be improved, and it is beneficial to control the particle size of the finished silicon-carbon composite material within an appropriate range, meet the performance requirements of the electrode processing, and improve the storage performance and dynamic performance of the battery.
[0134] In some embodiments, the silicon-containing material particles include a carbon substrate having a pore structure and a silicon-based material disposed in the pore structure of the carbon substrate.
[0135] The pore structure of the carbon substrate provides attachment sites for silicon-based materials, which can be used to store a large amount of silicon. The silicon-based materials uniformly dispersed in the pore structure of the carbon substrate are not easy to agglomerate. Furthermore, the carbon substrate has a certain mitigating effect on the volume change of the silicon-based materials arranged in the pore structure during the lithium insertion and extraction process, and can withstand the stress caused by the volume change of the silicon-based materials, so that the silicon-containing material particles have a low expansion rate and a highly stable structure, thereby improving the capacity, storage performance and cycle stability of the silicon-containing material particles. The internal area of the silicon-carbon composite material contains silicon-containing material particles of the above structure, which can not only improve the capacity of the battery, but also avoid the cracking of the silicon-carbon composite material during the cycle due to excessive volume expansion of the internal area, thereby improving the storage performance and cycle stability of the battery.
[0136] In some embodiments, the carbon substrate includes micropores with a pore size less than 2 nm, mesopores with a pore size of 2 nm-50 nm, and macropores with a pore size greater than 50 nm.
[0137] The pore structure of the carbon substrate can be tested using equipment and methods known in the art. For example, the pore size can be tested by a gas adsorption method in accordance with the GB / T19587-2017 & GB / T21650.2-2008 test standards, as follows: the porous material sample tube is immersed in liquid nitrogen at -196°C, and the nitrogen is adsorbed on the material to be tested at a relative pressure of 0-1. The pore size distribution of the porous material is characterized based on a relationship diagram between the volume of each pore size and the corresponding partial pressure, and the pore structure of the carbon substrate is characterized by the pore size distribution.
[0138] The above-mentioned pore structure in the carbon substrate helps the silicon-based material to adhere to the pore structure, and can effectively limit the volume expansion of the silicon-based material attached to the pore structure. Moreover, the silicon-based material after volume expansion will basically not cause damage to the pore structure of the carbon matrix, thereby increasing the capacity of the silicon-containing material particles while ensuring the stability of the structure.
[0139] In some embodiments, the pore volume of the micropores is greater than or equal to 0.5 cm 3 / g, optional 0.6cm 3 / g-0.9cm 3 / g.
[0140] The pore volume of the micropores can be measured using instruments and methods known in the art. For example, the test method can refer to GB / T19587-2004, using the mesopore pore size distribution test BJH (Barret joyner Halenda), using the gas adsorption and desorption method under the micro-mesopore model to test and select the adsorption branch data, and measure and count the total volume of pores with a pore size less than 2 nm.
[0141] In some embodiments, the pore volume of the micropores is 0.5 cm 3 / g, 0.55cm 3 / g, 0.6cm 3 / g, 0.65cm 3 / g, 0.7cm 3 / g, 0.75cm 3 / g, 0.8cm 3 / g, 0.85cm 3 / g, 0.9cm 3 / g, 0.95cm 3 / g, 1cm 3 / g or any range of values therebetween.
[0142] By regulating the pore volume size of the micropores in the carbon substrate, it is beneficial for the silicon-containing precursor to enter the pore structure of the carbon substrate, reducing the risk of silicon deposition on the surface of the carbon substrate, and improving the gram capacity and storage performance of the silicon-containing material particles.
[0143] In some embodiments, the average pore size of the carbon substrate is less than or equal to 5 nm, and can be 1 nm-3.5 nm.
[0144] The average pore size of the carbon substrate can be tested using equipment and methods known in the art. For example, the pore size can be tested using a gas adsorption method in accordance with the GB / T19587-2017 & GB / T21650.2-2008 test standards, as follows: the porous material sample tube is immersed in liquid nitrogen at -196°C, and the nitrogen is adsorbed on the material to be tested at a relative pressure of 0-1. The pore size distribution of the porous material is characterized based on a relationship diagram between the volume of each pore size and the corresponding partial pressure, thereby obtaining the average pore size of the carbon substrate.
[0145] In some embodiments, the average pore size of the carbon substrate is 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, or any range therebetween.
[0146] When the average pore size of the carbon substrate is within the above range, it is helpful for the adhesion of silicon-based materials, and the carbon substrate can limit the volume expansion of the silicon-based materials in the pores. The expanded silicon-based materials will not cause damage to the porous carbon matrix structure, thereby improving the capacity and structural stability of the silicon-containing material particles, and the battery has excellent storage performance and cycle stability.
[0147] In some embodiments, the specific surface area of the carbon substrate is greater than or equal to 1200 m 2 / g, optional 1500m 2 / g-1800m 2 / g.
[0148] In the present application, the specific surface area of the carbon substrate can be tested by methods known in the art. As an example, the specific surface area is tested by a gas adsorption method according to the GB / T19587-2017 test standard, specifically as follows: the sample tube is immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures is measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample is obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the solid.
[0149]
[0150] Where n a is the amount of adsorbed gas, in mol / g; p / p0 is the relative pressure; n m is the monolayer adsorption amount.
[0151] In some embodiments, the specific surface area of the carbon substrate is 1200 m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g or any range of values therebetween.
[0152] The specific surface area of the carbon substrate is within the above range. The carbon substrate has excellent pore volume and provides many sites for the deposition of silicon-based materials, which is beneficial to increasing the gram capacity of silicon-containing material particles.
[0153] In some embodiments, the silicon-based material includes at least one of elemental silicon, silicon-oxygen material, silicon-carbon material, and silicon-metal alloy.
[0154] In some embodiments, the silicon-based material includes silicon grains.
[0155] The crystal structure of silicon-based materials can be tested using equipment and methods known in the art. As an example, the following steps can be followed: select a microgrid of a certain diameter (such as a diameter of 3 mm), clamp the edge of the microgrid with pointed tweezers, and gently place it on white filter paper with the film surface facing up (the shiny surface is the film surface when observed under light); take an appropriate amount of sample (such as 1 g) and add it to a beaker containing an appropriate amount of ethanol, and perform ultrasonic oscillation for 10 minutes to 30 minutes; absorb it with a glass capillary, and then drop 2-3 drops of the sample to be tested onto the microgrid; after baking in an oven for 5 minutes, place the microgrid with the sample to be tested on the sample stage, and test it with a transmission electron microscope (such as Hitachi HF-3300S Cs-corrected STEM) at a certain magnification (for example, 60,000 times), and you can get a transmission electron microscope (TEM) image of the sample to be tested. If there are obvious lattice fringes (for example, the lattice spacing is approximately equal to 0.331 nm), it is crystalline silicon; if no lattice fringes are observed, it is amorphous silicon.
[0156] In the present application, the size of silicon grains can be measured according to the XRD pattern of the sample tested in accordance with the JIS / K0131-1996 test standard. According to the XRD pattern of the sample, the half-peak width β and the diffraction angle θ of the diffraction peak of the Si (111) crystal plane are taken and substituted into the Debye-Scherrer formula to calculate the particle size of the silicon grains. The Debye-Scherrer formula is as follows: Dhkl = kλ / (βcosθ), where Dhkl represents the particle size of the silicon grains, in nm; k represents the Scherrer constant, 0.89; λ represents the wavelength of the incident X-ray, 0.15406nm; β represents the half-peak width of the diffraction peak, in rad; θ represents the diffraction angle, in degrees.
[0157] In some embodiments, the size of the silicon grains is less than or equal to 10 nm. Optionally, the size of the silicon grains is less than or equal to 3 nm.
[0158] In some embodiments, the size of the silicon grains is 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or any range therebetween.
[0159] The size of silicon grains within the above range can avoid excessive local silicon enrichment due to excessive grain size, which may cause large expansion of silicon-containing material particles during lithium insertion and lead to cracking of the material, thereby improving the storage performance and cycle stability of the battery.
[0160] In some embodiments, the silicon-based material includes amorphous silicon.
[0161] Amorphous silicon can expand evenly in all directions, thereby causing uniform squeezing of the carbon substrate. The carbon substrate can effectively alleviate the volume expansion of amorphous silicon, thereby improving the storage performance and cycle stability of the battery.
[0162] In some embodiments, the carbon substrate includes at least one of graphite, soft carbon, and hard carbon.
[0163] In some embodiments, the carbon substrate is hard carbon.
[0164] In some embodiments, the pore volume of the hard carbon micropores is greater than or equal to 0.5 cm 3 / g, optional 0.6cm 3 / g-0.9cm 3 In some embodiments, the specific surface area of the hard carbon is greater than or equal to 1200 m 2 / g, optional 1500m 2 / g-1800m 2 In some embodiments, the average pore size of the hard carbon is less than or equal to 5 nm, and may be 1 nm to 3.5 nm.
[0165] When the micropore volume, specific surface area and average pore diameter of the hard carbon are within the above ranges, the hard carbon and the silicon-based material deposited in the pore structure work synergistically to enhance the gram capacity and structural stability of the silicon-containing material particles.
[0166] In some embodiments, based on the total mass of the silicon-containing material particles, the mass proportion of silicon in the silicon-containing material particles is 35%-50%, and optionally 35%-47%.
[0167] In some embodiments, based on the total mass of the silicon-containing material particles, the mass proportion of silicon in the silicon-containing material particles is 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or any value therebetween.
[0168] Based on the total mass of the silicon-containing material particles, the mass proportion of silicon in the silicon-containing material particles is within the above range, which is beneficial to improving the gram capacity and structural stability of the silicon-carbon composite material, and improving the cycle stability and storage performance of the battery.
[0169] In some embodiments, the porosity of the silicon-carbon composite material is 20%-45%, and optionally 20%-35%.
[0170] In the present application, the porosity of the silicon-carbon composite material can be tested by methods known in the art. As an example, the test is performed according to the GB / T24586 test standard, and the porosity P = (V2-V1) / V2*100%, the apparent volume V2 = S*H*A, where: S is the area, the unit is cm 2 ; H is the thickness, in cm; A is the number of samples, in EA; V1 is the true volume of the sample, in cm 3 ; V2 is the apparent volume of the sample, in cm 3 ;
[0171] The calculation method of the sample true volume V1 is as follows: place the sample in a true density tester (Accu Pyc II1340 analyzer), seal the test system, and introduce helium according to the procedure. By detecting the gas pressure in the sample chamber and the expansion chamber, and then according to the ideal gas state equation (v=nRT / P), the gas volumes of the sample chamber and the expansion chamber are obtained respectively, thereby obtaining the gas volume displaced by the sample under certain temperature and pressure conditions, which is the sample true volume V1.
[0172] In some embodiments, the porosity of the silicon-carbon composite material is 20%, 25%, 30%, 35%, 40%, 45%, or any range therebetween.
[0173] The porosity of the silicon-carbon composite material is within the above range, which reserves space for the volume change that occurs when the silicon-based material particles in the internal area insert and extract lithium. While taking into account the excellent gram capacity, the structural stability of the silicon-carbon composite material can be improved, thereby improving the energy density, storage performance and cycle stability of the battery.
[0174] In some embodiments, Dv50 of the silicon-carbon composite material is less than or equal to 16 μm, and can be optionally 8 μm-16 μm.
[0175] In some embodiments, the Dv50 of the silicon-carbon composite material is 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, or any range therebetween.
[0176] When the Dv50 of the silicon-carbon composite material is within the above range, the material has excellent dynamic properties and electrode processing performance, which is beneficial to improving the storage performance and cycle stability of the battery.
[0177] In some embodiments, the particle size distribution of the silicon-carbon composite material is (Dv90-Dv10) / Dv50 is 0.5-1.8, and can be optionally 0.8-1.5.
[0178] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the silicon-carbon composite material is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or any range therebetween.
[0179] When the particle size distribution of the silicon-carbon composite material is within the above range, the overall average particle size of the silicon-carbon composite material is relatively moderate, and the particle size distribution is relatively even, which is beneficial to improving the uniformity of the overall performance of the silicon-carbon composite material.
[0180] In some embodiments, the powder compaction density of the silicon-carbon composite material at 49000N is 0.7 g / cm 3 -1.3g / cm 3 , optional 0.95g / cm 3 -1.1g / cm 3
[0181] In this article, the term "powder compaction density" refers to the mass of powder particles per unit volume under a certain pressure.
[0182] In this application, the powder compaction density of the silicon-carbon composite material under a pressure of 49000N can be tested by a method known in the art. As an example, referring to GB / T24533-2009, 1g of silicon-carbon composite material powder is weighed and added to a bottom area of 1.327cm 2 The mold is pressurized to 5000 kg (equivalent to 49000 N), maintained for 30 seconds, then released and maintained for 10 seconds. The powder compaction density of the silicon-carbon composite material under a pressure of 49000 N is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).
[0183] In some embodiments, the powder compaction density of the silicon-carbon composite material at 49000N is 0.7 g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 or any range of values in between.
[0184] When the powder compaction density of the silicon-carbon composite material is within the above range, the negative electrode sheet has a higher compaction density, thereby further improving the energy density of the battery. In addition, the negative electrode film layer has a stronger ability to maintain the pore structure during the cycle, and the electrolyte wettability of the negative electrode sheet is better, which is conducive to improving the storage performance and cycle stability of the battery.
[0185] In some embodiments, the specific surface area of the silicon-carbon composite material is less than or equal to 6 m 2 / g, can be selected to be less than or equal to 4.5m 2 / g.
[0186] In some embodiments, the specific surface area of the silicon-carbon composite material is 1 m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g or any range of values therebetween.
[0187] When the specific surface area of the silicon-carbon composite material is within the above range, it helps to further reduce the contact area between the silicon-carbon composite material and the electrolyte, reduce the consumption of active ions in forming the SEI film, and improve the initial efficiency, storage performance and cycle stability of the battery.
[0188] The present application also provides a method for preparing a silicon-carbon composite material, comprising the following steps: providing silicon-containing material particles and carbon-based material particles; subjecting the silicon-containing material particles and a binder to a first spray granulation to obtain a first intermediate product; spraying the carbon-based material particles onto the surface of the first intermediate product to perform a second spray granulation to obtain the silicon-carbon composite material; the silicon-carbon composite material comprises an inner region and an outer region, the inner region being mainly composed of silicon-containing material particles, and the outer region being mainly composed of carbon-based material particles.
[0189] In this article, "spray granulation" refers to a granulation method in which a slurry or solution is sprayed into a granulation tower, and the slurry or solution is dried and agglomerated under the action of the spray hot air to obtain spherical granules. This method is widely used to produce catalysts of various particle sizes or other particles with certain particle size requirements. It can be used for experiments and small-scale production, with good granule ball precision and uniform particles.
[0190] By subjecting the silicon-containing material particles and the binder to a first spray granulation, the particle size of the silicon-containing material particles in the internal area of the silicon-carbon composite material can be controlled to obtain a first intermediate product in which the silicon-containing material particles are uniformly coated with the binder on the outside. By subjecting the carbon-based material particles to a second spray granulation and spraying them onto the surface of the first intermediate product, secondary particles can be obtained in which the inside is mainly silicon-containing material particles and the outside is mainly carbon-based material particles, and the carbon-based material particles tightly coat the silicon-containing material particles. Through two-step granulation, compared with the preparation method of simultaneously mixing and granulating silicon-containing material particles, a binder, and carbon-based material particles, the preparation method of the present application can achieve a state in which the silicon-containing material particles are completely coated by the carbon-based material particles, isolating the silicon from the contact with the electrolyte, and can regulate the porosity of the silicon-carbon composite material, thereby improving the storage performance and cycle stability of the battery.
[0191] In some embodiments, the silicon-containing material particles are prepared by the following steps: providing a gas containing a silicon precursor to a carbon substrate having a pore structure; and generating a silicon-based material attached to the pore structure from the silicon precursor by chemical vapor deposition to obtain the silicon-containing material particles.
[0192] In some embodiments, the silicon precursor includes at least one of silane, dichlorosilane, trichlorosilane, and tetrachlorosilane.
[0193] In some embodiments, the silicon precursor is silane.
[0194] In some embodiments, the mass ratio of the silicon-containing material particles to the binder is 1:2-2:1.
[0195] In some embodiments, the mass ratio of the silicon-containing material particles to the binder is 1:2, 1.5:2, 1:1, 1.5:1, 2:1 or any range therebetween.
[0196] When the mass ratio of silicon-containing material particles to adhesive is within the above range, the silicon-containing material particles and the carbon-based material particles have a good bonding effect, the particle size of the finished silicon-carbon composite material is within an appropriate range, and the battery has good storage performance and cycle stability while having excellent energy density.
[0197] In some embodiments, the mass ratio of the silicon-containing material particles to the carbon-based material particles is 1:12-1:6.
[0198] In some embodiments, the mass ratio of the silicon-containing material particles to the carbon-based material particles is 1:12, 1:11, 1:10, 1:9, 1:8, 1:7, 1:6 or any range therebetween.
[0199] When the mass ratio of silicon-containing material particles to carbon-based material particles is within the above range, the carbon-based material particles form a complete coating layer on the surface of the silicon-containing material particles to isolate silicon from the contact with the electrolyte, and the silicon-carbon composite material will not reduce its gram capacity due to excessive coating caused by an excessively high proportion of carbon-based material particles. The battery has excellent energy density, storage performance and cycle stability.
[0200] In some embodiments, the temperature difference between the inlet air temperature and the outlet air temperature of the first spray granulation is no more than 60°C.
[0201] In some embodiments, the temperature difference between the inlet air temperature and the outlet air temperature of the first spray granulation is 10°C, 20°C, 30°C, 40°C, 50°C, 60°C or any range therebetween.
[0202] Spray granulation relies on hot air drying of materials, and the drying state of the intermediate product is controlled by controlling the temperature of the hot air. Since the temperature of hot air drying is greatly affected by the environment, and the chamber only has a certain insulation effect but no heating effect, the temperature in the chamber is not an accurate temperature, but a temperature range. Setting the difference between the inlet and outlet temperatures within this range can ensure that the chamber temperature is within the appropriate range, and the actual temperature in the chamber will not be too low due to excessive temperature difference.
[0203] In some embodiments, the inlet air temperature is 110°C-150°C.
[0204] In some embodiments, the inlet air temperature is 110° C., 120° C., 130° C., 140° C., 150° C., or any range therebetween.
[0205] The temperature of the incoming air is the initial heat source in the chamber. Spray granulation relies on the incoming air to dry the material, ensuring that the silicon-containing material particles wrapped in the binder are in a semi-dry state, and preventing the silicon-containing material particles from sticking together due to excessive moisture due to low temperature, resulting in a larger particle size of the silicon-containing material in the inner area of the finished silicon-carbon composite material, and then the particle size of the finished silicon-carbon composite material is larger; or the temperature is too high and too dry to proceed to the next process. When the inlet air temperature is within the above range, the silicon-carbon composite material has good dynamic performance and pole piece processing performance.
[0206] In some embodiments, the outlet air temperature is 50°C-90°C.
[0207] In some embodiments, the outlet air temperature is 50° C., 60° C., 70° C., 80° C., 90° C., or any range therebetween.
[0208] The outlet air temperature is the result of comprehensive consideration of heat, which is determined by the inlet air temperature, feed rate, etc. Setting the outlet air temperature of the first spray granulation within this range can avoid the large temperature difference with the inlet air temperature causing the temperature in the chamber to be too low, and can also further make the first intermediate product in a semi-dry state, which is conducive to the next process.
[0209] In some embodiments, the feed gas pressure of the first spray granulation is 250 KPa-350 KPa, and can be optionally 280 KPa-320 KPa.
[0210] In some embodiments, the feed gas pressure of the first spray granulation is 250Kpa,
[0211] 251Kpa, 252Kpa, 253Kpa, 254Kpa, 255Kpa, 256Kpa, 257Kpa, 258Kpa, 259Kpa, 260Kpa or any numerical range therebetween.
[0212] The feed air pressure of the first spray granulation is a key step in controlling the particle size of the finished silicon-carbon composite material. When the feed air pressure is within the above range, the number and particle size of the silicon-containing material particles sprayed out can be controlled within an appropriate range to avoid the silicon-containing material particles being too large due to too low air pressure, which in turn causes the silicon-carbon composite material to have too large a particle size, deteriorating the dynamic performance and pole piece processing performance of the silicon-carbon composite material, and also avoiding the situation where some silicon-containing material particles are blocked at the spray gun nozzle and cannot be sprayed out due to too high air pressure. When the feed air pressure of the first spray granulation is within the above range, the particle size of the silicon-containing material sprayed out can be within an appropriate range, reaching a state where the number of silicon-containing material particles in the internal area of the silicon-carbon composite material does not exceed 3, which is beneficial to improving the storage performance and pole piece processing performance of the silicon-carbon composite material.
[0213] In some embodiments, the temperature difference between the inlet air temperature and the outlet air temperature of the second spray granulation is 20°C-40°C.
[0214] In some embodiments, the temperature difference between the inlet air temperature and the outlet air temperature of the second spray granulation is 20°C, 24°C, 28°C, 32°C, 36°C, 40°C or any range therebetween.
[0215] In some embodiments, the inlet air temperature of the second spray granulation is 170°C-280°C.
[0216] In some embodiments, the inlet air temperature of the second spray granulation is 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C or any range therebetween.
[0217] The air inlet temperature of the second spray granulation step is a key step in controlling the strength and structural stability of the silicon-carbon composite material. Since the first intermediate product has a certain viscosity, it is necessary to quickly coat the carbon-based material particles to form secondary particles and dry them to avoid the first intermediate product and secondary particles from agglomerating or bonding together during the process due to low temperature. It can also avoid the binder shrinking too fast or failing due to high temperature, which will not produce a good bonding effect. When the air inlet temperature of the second spray granulation is within this range, the prepared silicon-carbon composite material has a suitable particle size, excellent strength and structural stability, and plays a role in stabilizing the storage performance and cycle performance during the battery's life cycle.
[0218] In some embodiments, the outlet air temperature of the second spray granulation is 130°C-240°C.
[0219] In some embodiments, the outlet air temperature of the second spray granulation is 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or any range therebetween.
[0220] In some embodiments, the feed gas pressure of the second spray granulation is 150 KPa-260 KPa, and can be optionally 180 KPa-210 KPa.
[0221] In some embodiments, the feed gas pressure of the second spray granulation is 150 Kpa, 160 Kpa, 170 Kpa, 180 Kpa, 190 Kpa, 200 Kpa, 210 Kpa, 220 Kpa, 230 Kpa, 240 Kpa, 250 Kpa, 260 Kpa or any range therebetween.
[0222] The feed pressure of the second spray granulation is a key step to control the integrity and uniformity of the carbon-based material particles covering the silicon-containing material particles. The feed pressure of the second spray granulation is within the above range, which can improve the storage performance and cycle stability of the battery. It can avoid excessive carbon-based material particles wrapped outside the silicon-containing material due to excessive pressure and too fast feed speed, resulting in too many carbon-based material particles, and the particle size of the finished silicon-carbon composite material is too large, thereby deteriorating the dynamic performance, pole piece processing performance and gram capacity of the silicon-carbon composite material; it can also avoid that due to too low pressure and too slow feed speed, some silicon-containing material particles cannot be completely covered by carbon-based material particles, and the contact between silicon and electrolyte cannot be completely isolated, which weakens the storage performance of the silicon-carbon composite material. .
[0223] In some embodiments, the method for preparing the silicon-carbon composite material further comprises: introducing a gaseous carbon source after the second spray granulation, and carbonizing after gas phase coating to obtain the silicon-carbon composite material.
[0224] The secondary particles formed by carbon-based material particles coating silicon-containing material particles have more bumps on the surface and a larger specific surface area. After carbon coating, the specific surface area of the silicon-carbon composite material can be controlled within an appropriate range, so that the battery has excellent storage performance, cycle stability and first effect; and the carbon coating layer in the external area can further reduce the possibility of contact between silicon and electrolyte, and the storage performance of the battery is further improved.
[0225] In some embodiments, the gaseous carbon source includes a gas-phase hydrocarbon, which may be at least one of methane, ethylene, and acetylene.
[0226] In some embodiments, the gaseous carbon source is acetylene.
[0227] The temperature at which the gaseous carbon source decomposes to form the carbon coating layer is within a suitable range, satisfying the temperature requirements of various components of the silicon-carbon composite material.
[0228] In some embodiments, the carbonization temperature is 400°C-800°C.
[0229] In some embodiments, the carbonization temperature is 400° C., 500° C., 600° C., 700° C., 800° C., or any range therebetween.
[0230] When the carbonization temperature is within the above range, the gaseous carbon source can decompose to produce carbides that coat the surface of the secondary particles to form a carbon coating layer, which can reduce the specific surface area of the secondary particles while further isolating the contact between silicon and the electrolyte, thereby improving the storage performance and cycle stability of the battery; it can also avoid the silicon in the silicon-containing material particles from generating silicon carbide that cannot provide capacity due to excessively high temperature, thereby achieving the purpose of not losing the gram capacity of the silicon-carbon composite material.
[0231] In some embodiments, the carbonization time is 0.2h-2h.
[0232] In some embodiments, the carbonization time is 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h or any range therebetween.
[0233] When the carbonization time is within the above range, the silicon-carbon composite material has a suitable specific surface area and excellent capacity, which can avoid the problem that the amorphous carbon coating is too small due to too short a time, and the surface of the secondary particles cannot be completely covered to achieve the purpose of reducing the specific surface area; it can also avoid the problem that the carbonization time is too long, which greatly increases the risk of silicon generating silicon carbide under long-term high temperature, resulting in loss of capacity of the silicon-carbon composite material.
[0234] In some embodiments, the protective gas during the carbonization process is nitrogen or argon. Optionally, the gas flow ratio of the gaseous carbon source to the protective gas is 1:5 to 1:1.5.
[0235] In some embodiments, the gas flow ratio of the gaseous carbon source to the protective gas is 1:5, 1:4.5, 1:4, 1:3.5, 1:3, 1:2.5, 1:2, 1:1.5 or any range therebetween.
[0236] When the airflow ratio of the gaseous carbon source to the protective gas is within the above range, the silicon-carbon composite material has excellent processing efficiency and suitable specific surface area, which can avoid the long coating time and slow production efficiency caused by the too low airflow ratio; and can also avoid the too high airflow ratio, which leads to the gaseous carbon source decomposing too quickly, and is easy to be locally enriched on the surface of the secondary particles, and cannot form a uniform amorphous carbon coating layer, and cannot effectively reduce the specific surface area of the silicon-carbon composite material.
[0237] In some embodiments, the binder includes at least one of phenolic resin, styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, sodium alginate, carboxymethyl cellulose, polyacrylonitrile, and polypropylene alcohol.
[0238] In some embodiments, the binder includes a phenolic resin.
[0239] On the one hand, the above-mentioned binder can provide bonding force between the silicon-containing material particles and the carbon-based material particles. On the other hand, it will shrink due to heat in the second spray granulation step to form pores and retain functional groups that exert bonding properties and remove volatiles in the carbonization step, thereby making the silicon-carbon composite material have a certain porosity, reserving space for the expansion of the silicon-containing material particles, and improving the storage performance and cycle stability of the battery.
[0240] [Negative electrode]
[0241] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon composite material in some embodiments or a silicon-carbon composite material prepared by a preparation method in some embodiments.
[0242] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0243] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0244] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0245] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0246] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0247] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0248] [Positive electrode]
[0249] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.
[0250] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0251] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0252] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333)、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0253] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0254] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0255] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0256] [Electrolytes]
[0257] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0258] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0259] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0260] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0261] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0262] [Isolation film]
[0263] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0264] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0265] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0266] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0267] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0268] In the present application, the shape of the secondary battery includes but is not limited to cylindrical, square or other arbitrary shapes. For example, Figure 1 The secondary battery 5 is a square structure as an example.
[0269] In some embodiments, reference Figure 2 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0270] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0271] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0272] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0273] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0274] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0275] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0276] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0277] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0278] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0279] Example
[0280] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0281] 1. Preparation method
[0282] Preparation Example 1: Silicon-containing material particles 1
[0283] At 465°C, a gas containing silane SiH4 is introduced into a hard carbon substrate with a porous structure, and vapor deposition is performed for 10 hours. By chemical vapor deposition, a silicon-based material deposited in the porous structure of the hard carbon substrate is generated from silane. Then, chemical vapor deposition is used to vapor deposit on the hard carbon substrate for 0.5 hours at 660°C using a carbon source gas and a protective gas with a gas flow ratio of 1:2. A carbon layer accounting for 3% of the total mass of the hard carbon substrate and the deposited silicon-based material is coated on the outer surface of the hard carbon substrate, wherein the gas source is acetylene gas, and silicon-containing material particles 1 are obtained. Among them, the mass ratio of silicon in silane to hard carbon substrate is 1:1; the pore volume of the micropores of the hard carbon substrate is 0.8cm 3 / g, average pore size is 3.2nm, specific surface area is 1612m 2 / g, the silicon-based material comprises silicon grains, and the particle size of the silicon grains is 2.9nm; the Dv50 of the silicon-containing material particles 1 is 4.2μm, and the silicon mass percentage is 46%.
[0284] Preparation Example 2: Silicon-containing material particles 2
[0285] At 465°C, a gas containing silane SiH4 is introduced into a hard carbon substrate with a porous structure for 8 hours of vapor deposition. By chemical vapor deposition, a silicon-based material deposited in the porous structure of the hard carbon substrate is generated from silane. Then, chemical vapor deposition is used to vapor deposit on the hard carbon substrate for 0.5 hours at 660°C using a carbon source gas and a protective gas with a gas flow ratio of 1:2. A carbon layer accounting for 3% of the total mass of the hard carbon substrate and the deposited silicon-based material is coated on the surface of the hard carbon particles, wherein the gas source is acetylene gas, and silicon-containing material particles 2 are obtained. Among them, the mass ratio of silicon in silane to hard carbon substrate is 2:3; the pore volume of the micropores of the hard carbon substrate is 0.8cm 3 / g, average pore size is 3.2nm, specific surface area is 1612m 2 / g, the silicon-based material comprises silicon grains, and the particle size of the silicon grains is 2.9nm; the silicon mass percentage of the silicon-containing material particles 2 is 36%.
[0286] Preparation Example 3: Silicon-containing material particles 3
[0287] At 465°C, a gas containing silane SiH4 is introduced into a hard carbon substrate with a porous structure for 9 hours of vapor deposition. By chemical vapor deposition, a silicon-based material deposited in the porous structure of the hard carbon substrate is generated from silane. Then, chemical vapor deposition is used to vapor deposit on the hard carbon substrate for 0.5 hours at 660°C using a carbon source gas and a protective gas with a gas flow ratio of 1:2. A carbon layer accounting for 3% of the total mass of the hard carbon substrate and the deposited silicon-based material is coated on the surface of the hard carbon particles, wherein the gas source is acetylene gas, and silicon-containing material particles 3 are obtained. Among them, the mass ratio of silicon in silane to hard carbon substrate is 2:3; the pore volume of the micropores of the hard carbon substrate is 0.4cm 3 / g, average pore size is 3.5nm, specific surface area is 1408m 2 / g, the silicon-based material comprises silicon grains, and the particle size of the silicon grains is 3.0nm; the mass percentage of silicon in the silicon-containing material particles 3 is 35%.
[0288] Example 1
[0289] 1) Preparation of silicon-carbon composite materials
[0290] The silicon-containing material particles 1 and the phenolic resin are mixed in a mass ratio of 1:1.2, and placed in a feed bin 1 of a spraying device. Under nitrogen protection, the feed bin 1 is set to have an air pressure of 300 KPa, an air inlet temperature of 130°C, and an air outlet temperature of 70°C to obtain an intermediate product, i.e., a first intermediate product of a semi-dried coated adhesive;
[0291] Graphite with a Dv50 of 3.8 um and the intermediate product prepared above are placed in a feed bin 2, the mass ratio of graphite to silicon-containing material particles is 9:1, the air pressure of the feed bin 2 is set to 200 KPa, the air inlet temperature is 210°C, and the air outlet temperature is 170°C, to obtain secondary particles whose inner region is mainly composed of silicon-containing material particles and whose outer region is mainly composed of graphite material particles;
[0292] The secondary particles are placed in a heating chamber, and the heating chamber is first heated to 660°C in a nitrogen atmosphere, and then a mixed gas is introduced at a volume ratio of 1:2 between nitrogen and acetylene gas, and the mixture is kept warm for 0.5 hours. The surface of the secondary particles is carbon-coated to obtain a silicon-carbon composite material. Among them, the silicon element mass proportion in the area r / 2 from the geometric center of the silicon-carbon composite material is 45%, the carbon element mass proportion in the area extending from the outer surface to the inside by a distance of r / 2 is 98%, the porosity is 28%, the Dv50 is 13.1um, the particle size distribution is 1.5, and the powder compaction density of the silicon-carbon composite material under 49000N is 1.02g / cm 3 , specific surface area is 4.3m 2 / g.
[0293] 2) Preparation of negative electrode sheet
[0294] The prepared silicon-carbon composite material, artificial graphite, conductive carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 20:75:2:2:1 to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative electrode current collector copper foil with a thickness of 13 μm, the coating speed is 25 m / min, and the temperature of the coating oven is 110°C; and then the negative electrode sheet is obtained by cold pressing and slitting.
[0295] 3) Preparation of positive electrode
[0296] The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system in a weight ratio of 96:2:2 to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on a positive electrode current collector aluminum foil with a thickness of 13 μm at a coating speed of 30 m / min; the temperature of the coating oven is 110°C, and then the positive electrode sheets are obtained through cold pressing and slitting.
[0297] 4) Preparation of electrolyte
[0298] In an argon atmosphere glove box (H2O content <0.1ppm, O2 content <0.1ppm), lithium hexafluorophosphate LiPF6 was dissolved in a mixed system of organic solvents ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of the two was 3:7), and stirred evenly to obtain an electrolyte with a lithium salt concentration of 1 mol / L. Then fluoroethylene carbonate (FEC) was added, and the content of FEC was 5% of the total mass of the electrolyte.
[0299] 5) Isolation film
[0300] Polypropylene (PP) film is used as the isolation film.
[0301] 6) Preparation of batteries
[0302] The positive electrode sheet, the isolation film, and the composite negative electrode sheet are stacked in order, so that the isolation film is placed in the middle of the positive and negative electrode sheets to isolate the positive and negative electrode sheets, and the electrode assembly is wound, the pole ears are welded, and the electrode assembly is placed in an outer package, and then the electrolyte is injected and sealed. After standing, cold pressing, formation, shaping, capacity testing and other processes, the lithium-ion secondary battery prepared in Example 1 is obtained.
[0303] Example 2
[0304] The preparation method of the battery of Example 2 is similar to that of the battery of Example 1, except that silicon-containing material particles 2 are used, as shown in Table 1.
[0305] Embodiment 3-10
[0306] The preparation methods of the batteries of Examples 3-10 are similar to those of the batteries of Example 1, except that the preparation parameters of the silicon-carbon composite material and / or the Dv50 of the graphite particles are adjusted, as shown in Table 1.
[0307] Embodiment 11
[0308] The preparation method of the battery of Example 11 is similar to that of the battery of Example 1, except that the Dv50 of the graphite particles is adjusted, as shown in Table 1.
[0309] Example 12
[0310] The preparation method of the battery of Example 12 is similar to that of the battery of Example 1, except that silicon-containing material particles 3 are used, as shown in Table 1.
[0311] Table 1
[0312]
[0313] Comparative Example 1
[0314] The preparation method of the battery of Comparative Example 1 is similar to that of the battery of Example 1, except that the silicon-carbon composite material is secondary particles obtained by directly mixing and granulating silicon-containing material particles and graphite. The specific preparation method is:
[0315] Using the same graphite and silicon-containing material particles as in Example 1, the graphite, silicon-containing material particles, and phenolic resin were mixed in a ratio of 9:1:1.2, placed in a feed bin of a spray device, and under nitrogen protection, the air pressure of the feed bin 2 was set to 150 KPa, the air inlet temperature was set to 210° C., and the air outlet temperature was set to 170° C. to obtain secondary particles;
[0316] The above secondary particles are placed in a heating chamber. In a nitrogen atmosphere, the heating chamber is first heated to 660°C, and then a mixed gas is introduced at a volume ratio of nitrogen to acetylene of 1:2. The mixture is kept warm for 0.5 h, and the surface of the secondary particles is carbon-coated to obtain a silicon-carbon composite material.
[0317] Comparative Example 2
[0318] The preparation method of the battery of Comparative Example 2 is similar to that of the battery of Example 1, except that the silicon-carbon composite material is a direct mixture of silicon-containing material particles and graphite. The specific preparation method is:
[0319] The same graphite and silicon-containing material particles as those in Example 1 were used, and the graphite and silicon-containing material particles were dry-mixed uniformly in a ratio of 9:1 to obtain a mixed powder.
[0320] 2. Test Method
[0321] 1. Gram capacity test of silicon-carbon composite materials
[0322] Cell production: button cells were produced, with lithium sheets used as the positive electrode; the prepared silicon-carbon composite material, conductive carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) were fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:2:2:1 to obtain a negative electrode slurry, which was evenly coated on a negative electrode current collector copper foil with a thickness of 13 μm at a coating speed of 25 m / min and a coating oven temperature of 110°C; then the negative electrode sheets were obtained by cold pressing and slitting; in an argon atmosphere glove box (H2O content <0.1 ppm, O2 content <0.1 ppm), lithium salt lithium hexafluorophosphate LiPF6 was dissolved in a mixed system of organic solvents ethylene carbonate (EC) and diethyl carbonate (DEC) (EC:DEC volume ratio of 3:7), and stirred evenly to obtain an electrolyte with a lithium salt concentration of 1 mol / L; a 9 μm polyethylene (PE) film was used as an isolation membrane. The above-mentioned positive electrode, separator, negative electrode and electrolyte are assembled into a battery for testing.
[0323] Test process: Under normal temperature conditions, let the battery stand for 3 hours, then discharge at a constant current of 0.05C to a voltage of 0.005V, and further discharge at a constant current of 50μA to a voltage of 0.005V, and record the capacity at this time as the lithium insertion capacity. Let it stand for 5 minutes, and then charge at a rate of 0.1C to a voltage of 0.8V, and record the capacity at this time as the lithium removal capacity, that is, the material capacity. The ratio of the lithium removal capacity to the mass of the silicon-carbon composite material is the gram capacity of the silicon-carbon composite material.
[0324] 2. Battery room temperature cycle performance test
[0325] Test process: At 25°C, let the battery stand for 30 minutes, then charge at 0.5C rate to 4.2V, further charge at 4.2V constant voltage to 0.05C, let stand for 5 minutes, then discharge at 0.5C rate to 2.8V, the obtained capacity is recorded as initial capacity C0, this is a charge and discharge cycle process. Repeat the above steps for the same battery, record the discharge capacity Cn in each cycle, then the battery capacity retention rate Pn after each cycle = Cn / C0*100%, until Pn≦80%, stop the test, and record the number of cycles at this time.
[0326] 3. Battery high temperature storage performance test
[0327] Test conditions: Store the fully charged battery cells at 60°C and test the capacity every 30 days until the capacity decays to 80% of the initial capacity. Record the storage days at this time.
[0328] Test process: let the battery stand for 30 minutes, discharge at 0.5C rate to 2.8V, let it stand for 5 minutes, then charge at 0.5C rate to 4.2V, further charge at 4.2V constant voltage to 0.05C, let it stand for 5 minutes, then discharge at 0.5C rate to 2.8V, this is the test capacity process, and record each discharge capacity. Let the battery stand for another 5 minutes, then charge at 0.5C rate to 4.2V, further charge at 4.2V constant voltage to 0.05C, this is to fully charge the battery, then put it in a 60℃ incubator, and test the capacity according to the above process after 30 days.
[0329] Capacity retention rate after storage for n days (%) = (discharge capacity on the nth day / first discharge capacity on day 0) × 100%. When the capacity retention rate is ≤ 80%, stop the test and record the number of storage days at this time. With the number of days as the x-axis and the capacity retention rate as the y-axis, draw a fitting curve to obtain the number of storage days when the capacity retention rate is 80%.
[0330] III. Analysis of test results of various embodiments and comparative examples
[0331] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The results are shown in the table below.
[0332] As can be seen from Table 2, the inner area of the silicon-carbon composite material is mainly silicon material particles, and the outer area is mainly graphite particles. This structure can improve the high-temperature storage performance and cycle stability of the battery. At the same time, the silicon-carbon composite material has excellent capacity.
[0333] Table 2
[0334]
[0335]
[0336] It can be seen from Tables 3 and 4 that when the mass proportion of silicon elements in the region r / 2 from the geometric center of the silicon-carbon composite material is greater than or equal to 30%, the silicon-carbon composite material has excellent gram capacity, and the battery has excellent high-temperature storage performance and cycle stability. When the Dv50 of the silicon-carbon composite material is less than or equal to 16μm, the battery has good high-temperature storage performance and cycle stability.
[0337] Table 3
[0338]
[0339] Table 4
[0340]
[0341] It can be seen from Table 5 that when the mass proportion of carbon elements in the area extending from the surface of the silicon-carbon composite material to the inside by a distance r / 2 is greater than or equal to 80%, the battery has excellent high-temperature storage performance and cycle stability, and the silicon-carbon composite material also has excellent gram capacity.
[0342] Table 5
[0343]
[0344]
[0345] It can be seen from Table 6 that when the porosity of the silicon-carbon composite material is 20%-45%, the silicon-carbon composite material has excellent gram capacity, and the battery has excellent high-temperature storage performance and cycle stability.
[0346] Table 6
[0347]
[0348] From the comparison between Example 1 and Example 11 in Table 7, it can be seen that when the Dv50 of the silicon-containing material particles is greater than the Dv50 of the graphite particles, the high-temperature storage performance of the battery can be improved. From the comparison between Example 1 and Example 12 in Table 7, it can be seen that the pore volume of the carbon substrate micropores in the silicon-containing material particles is greater than or equal to 0.5 cm 3 / g, the silicon-carbon composite material has a better gram capacity, and the battery has both excellent high-temperature storage performance and cycle performance.
[0349] Table 7
[0350]
[0351] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material comprises an inner region and an outer region, wherein the inner region is mainly composed of silicon-containing material particles, and the outer region is mainly composed of carbon-based material particles.
2. The silicon-carbon composite material according to claim 1, characterized in that: The number of silicon-containing material particles in the inner region is less than or equal to 3, and can be 1-2.
3. The silicon-carbon composite material according to claim 1 or 2, characterized in that: The mass proportion of silicon element in the region r / 2 from the geometric center of the silicon-carbon composite material is greater than or equal to 30%, and can be optionally 35%-45%, wherein r represents the short diameter of the silicon-carbon composite material.
4. The silicon-carbon composite material according to any one of claims 1 to 3, characterized in that: The mass proportion of carbon elements in the region extending from the outer surface of the silicon-carbon composite material to the inner side by a distance r / 2 is greater than or equal to 80%, and can be optionally 90%-100%, wherein r represents the short diameter of the silicon-carbon composite material.
5. The silicon-carbon composite material according to any one of claims 1 to 4, characterized in that: The outer region of the silicon-carbon composite material also includes an amorphous carbon coating layer.
6. The silicon-carbon composite material according to any one of claims 1 to 5, characterized in that: The Dv50 of the silicon-containing material particles is greater than or equal to the Dv50 of the carbon-based material particles.
7. The silicon-carbon composite material according to any one of claims 1 to 6, characterized in that: The Dv50 of the silicon-containing material particles is less than or equal to 5 μm; and / or, The Dv50 of the carbon-based material particles is less than or equal to 5 μm.
8. The silicon-carbon composite material according to any one of claims 1 to 7, characterized in that: The silicon-containing material particles include at least one of elemental silicon, silicon-oxygen material, silicon-carbon material, and silicon-metal alloy. Optionally, the silicon-containing material particles include silicon-carbon material; And / or, the carbon-based material particles include at least one of artificial graphite and natural graphite. Optionally, the carbon-based material particles include artificial graphite.
9. The silicon-carbon composite material according to any one of claims 1 to 8, characterized in that: The silicon-containing material particles include a carbon substrate having a pore structure and a silicon-based material disposed in the pore structure of the carbon substrate.
10. The silicon-carbon composite material according to claim 9, characterized in that: The carbon substrate comprises micropores with a pore size less than 2 nm, mesopores with a pore size of 2 nm-50 nm, and macropores with a pore size greater than 50 nm.
11. The silicon-carbon composite material according to claim 10, characterized in that: The pore volume of the micropores is greater than or equal to 0.5 cm 3 / g, optional 0.6cm 3 / g-0.9cm 3 / g.
12. The silicon-carbon composite material according to any one of claims 9 to 11, characterized in that: The average pore size of the carbon substrate is less than or equal to 5 nm, and can be 1 nm-3.5 nm.
13. The silicon-carbon composite material according to any one of claims 9 to 12, characterized in that: The specific surface area of the carbon substrate is greater than or equal to 1200 m 2 / g, optional 1500m 2 / g-1800m 2 / g.
14. The silicon-carbon composite material according to any one of claims 9 to 13, characterized in that: The silicon-based material includes at least one of elemental silicon, silicon-oxygen material, silicon-carbon material, and silicon-metal alloy; the carbon substrate includes at least one of graphite, soft carbon, and hard carbon.
15. The silicon-carbon composite material according to any one of claims 9 to 14, It is characterized in that The silicon-based material includes silicon grains. Optionally, the size of the silicon grains is less than or equal to 10 nm. Optionally, the size of the silicon grains is less than or equal to 3 nm.
16. The silicon-carbon composite material according to any one of claims 1 to 15, It is characterized in that The porosity of the silicon-carbon composite material is 20%-45%, and can be optionally 20%-35%.
17. The silicon-carbon composite material according to any one of claims 1 to 16, It is characterized in that The silicon-carbon composite material also satisfies at least one of the following conditions: (1) The volume distribution particle size Dv50 of the silicon-carbon composite material is less than or equal to 16 μm, and can be selected to be 8 μm-16 μm; (2) The particle size distribution of the silicon-carbon composite material (Dv90-Dv10) / Dv50 is 0.5-1.8, and can be optionally 0.8-1.5; (3) The powder compaction density of the silicon-carbon composite material at 49000N is 0.7g / cm 3 -1.3g / cm 3 , optional 0.95g / cm 3 -1.1g / cm 3 ; (4) The specific surface area of the silicon-carbon composite material is less than or equal to 6 m 2 / g, can be selected to be less than or equal to 4.5m 2 / g.
18. A method for preparing a silicon-carbon composite material, characterized in that: The steps include: Providing silicon-containing material particles and carbon-based material particles; Performing a first spray granulation on the silicon-containing material particles and the binder to obtain a first intermediate product; Spraying carbon-based material particles onto the surface of the first intermediate product to perform a second spray granulation to prepare the silicon-carbon composite material; The silicon-carbon composite material includes an inner region and an outer region, the inner region is mainly composed of silicon-containing material particles, and the outer region is mainly composed of carbon-based material particles.
19. The preparation method according to claim 18, characterized in that: The silicon-containing material particles are prepared by the following steps: providing a gas containing a silicon precursor to a carbon substrate having a porous structure; The silicon-based material attached to the pore structure is generated from the silicon precursor by chemical vapor deposition to obtain the silicon-containing material particles.
20. The preparation method according to claim 18 or 19, characterized in that: The mass ratio of the silicon-containing material particles to the binder is 1:2-2:1; and / or, The mass ratio of the silicon-containing material particles to the carbon-based material particles is 1:12-1:
6.
21. The preparation method according to any one of claims 18 to 20, characterized in that: The first spray granulation satisfies at least one of the following conditions: (1) The temperature difference between the inlet air temperature and the outlet air temperature is not greater than 60°C; (2) The air inlet temperature is 110℃-150℃; (3) The air outlet temperature is 50℃-90℃; (4) The feed gas pressure is 250KPa-350KPa, and can be optionally 280KPa-320KPa.
22. The preparation method according to any one of claims 18 to 21, characterized in that: The second spray granulation satisfies at least one of the following conditions: (1) The temperature difference between the inlet air temperature and the outlet air temperature is 20℃-40℃; (2) The inlet air temperature is 170℃-280℃; (3) The air outlet temperature is 130℃-240℃; (4) The feed gas pressure is 150KPa-260KPa, and can be optionally 180KPa-210KPa.
23. The preparation method according to any one of claims 18 to 22, characterized in that: The method for preparing the silicon-carbon composite material further comprises: After the second spray granulation, a gaseous carbon source is introduced, and carbonization is performed after gas phase coating to obtain the silicon-carbon composite material.
24. The preparation method according to claim 23, characterized in that: The gaseous carbon source is introduced, and carbonization is performed after gas phase coating to obtain the silicon-carbon composite material that satisfies at least one of the following conditions: (1) The gaseous carbon source includes a gaseous hydrocarbon alkane, which can be at least one of methane, ethylene, and acetylene; (2) The carbonization temperature is 400° C.-800° C.; (3) The carbonization time is 0.2h-2h; (4) During the carbonization process, the protective gas is nitrogen or argon. Optionally, the gas flow ratio of the gaseous carbon source to the protective gas is 1:5 to 1:1.
5.
25. The preparation method according to any one of claims 18 to 24, characterized in that: The binder includes at least one of phenolic resin, styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, sodium alginate, carboxymethyl cellulose, polyacrylonitrile and polypropylene alcohol.
26. A secondary battery, characterized in that: The secondary battery comprises a negative electrode plate, and the negative electrode plate comprises the silicon-carbon composite material according to any one of claims 1 to 17 or the silicon-carbon composite material prepared by the preparation method according to any one of claims 18 to 25.
27. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 26.
Citation Information
Patent Citations
Method for preparing silicon carbide composite particles and application thereof as cathode material of lithium ion battery
CN101931076A
Lithium ion battery composite anode material and preparation method thereof
CN102244240A
Porous silicon carbon negative electrode material, a preparation method thereof and a lithium ion battery
CN109273680A
Preparation method of silicon based negative electrode material of lithium ion battery
CN110844910A
Silicon-carbon negative electrode material with in-situ growth onion carbon layer structure and preparation method of silicon-carbon negative electrode material
CN115642231A
Cited By
Silicon-carbon composite material, preparation method, secondary battery, and electric device
EP4800760A1